Retracer une démarche de médiation paysagère pour mieux l’évaluer : expérimentation dans un secteur à controverses environnementales. Les Ateliers Grand site Marais mouillé poitevin - Alexis Pernet (Développement Durable et Territoires)
This paper describes a landscape mediation process, led in a marsh area (Marais poitevin, France), a territory known for long term environmental controversies. One of his emblematic site (Marais mouillé) is going to be strongly affected under the influence of a pathology of the common Ash tree (Chalara fraxinea). To visualize the mediation process, an experimental representation is suggested from the combination of several dimensions (chronological, sensitive and methodological), in the objective to propose a reflexive approach, but also defining a system of tracks which would allow a future evaluation. The relation between landscape project, mediation and environmental controversy makes the object of a final development to discuss process results.